Prevalence of Deep Surgical Site Infection After Repair of Periarticular Knee Fractures - Muhammad Adam, Muhammad Adam; Muhammad Rizky, Muhammad Rizky (The Indonesian Journal of General Medicine, 2024)
Background: The prevalence of deep surgical site infections (SSIs) following the repair of periarticular knee fractures is a critical area of investigation within orthopedic surgery, as it significantly impacts patient outcomes and healthcare costs. The literature surrounding this topic reveals a complex interplay of risk factors and outcomes associated with SSIs, as well as varying rates of infection depending on the type of fracture. Literature Review: The investigation into the prevalence of deep surgical site infections (SSIs) following the repair of periarticular knee fractures reveals significant insights into the risk factors and outcomes associated with these infections. The literature highlights a critical need for orthopedic surgeons to understand the varying rates of SSIs depending on fracture types, as well as the complex interplay of risk factors that contribute to these complications. While both studies effectively illuminate the challenges associated with SSIs, there remains an opportunity for further exploration into specific interventions that could reduce infection rates. By providing concrete recommendations based on their findings, future research could enhance clinical practice and contribute to improved patient care. Conclusion: In conclusion, the literature reveals a pressing need to address the prevalence and risk factors of deep SSIs in orthopedic surgery, particularly following the repair of periarticular knee fractures. Understanding these dynamics is crucial for developing effective prevention strategies, ultimately aiming to enhance patient outcomes and reduce the economic burden associated with these infections.